Penetapan harga pokok penjualan berdasarkan pemerolehan laba dan menentukan aktiva - Surya Indah Puspita, Dwi; Erstiawan, Martinus Sony; Soebijono, Tony; Puji Widodo, Arifin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to determine the cost of goods sold to increase profits and determine assets. The object of research is small businesses engaged in the industry of making bags, wallets, and suitcases. The method used uses descriptive qualitative where interviews and data documentation are used as the basis for calculating the main production, inventory, determination of fifo methods, raw material costs, labor and factory overhead. The result achieved is that the determination of the cost of goods sold in the bag industry is the main thing because it can decompose the cost of production starting from raw materials, direct labor costs and factory overhead used. From this determination, the profit generated increases and increases in current asset activity. Further research to be developed to be able to compare the cost of goods sold from the production process itself and the purchase of merchandise with the same type of business and goods.